Evaluation of Stylosanthes hamata (L.) Taub. accessions for livestock and crop enterprises in subhumid Nigeria - Tarawali, Shirley A. (Commonwealth Scientific and Industrial Research Organisation, 1995)
Stylosanthes species have featured prominantly in the forage evaluation program at Kaduna in the subhumid zone of Nigeria. This paper describes the evaluation of an Australian collection of 163 S. hamata accessions using small plot observations, agronomic trials, and assessment of the effects of selected accessions on maize production. Accessions comparable, or superior, to S. hamata cVerano, which is currently used for pasture developments, include ILCA 15876 (CPI 110073) and ILCA 15868 (CPI 110063), both of which remained greener in the dry season and had higher biomass yields.